Artificial Nociceptor Using Liquid Ionic Memory - Sial, Qadeer Akbar; Kumar, Mohit; Iqbal, Shahid; Kalanur, Shankara S.; Seo, Hyungtak (Advanced Electronic Materials, 2022)
The incorporation of the different functions of a biological nervous system into electronic devices is challenging in the realization of humanoid robotics, which can recognize and respond in a manner that is similar to humans. Emerging synaptic devices that can process electronic signals by neuromorphic functions that operate in a similar manner to that of biological nervous systems. In this study, an acid-sensitive artificial nociceptor device, which simultaneously detects acid concentration and generates synaptic signals, is developed for electronic nose application. The transition metal oxide (WO3)-based device electrochemically performs neuromorphic sulfuric acid (H2SO4) sensing. The current–voltage curves demonstrate loop opening, with the change in the molarity of the acid, indicating memory storage ability and tunability of the developed nociceptor device.
Keywords: Acid sensitives; Artificial nociceptor; Electrochemicals; Electronic signals; Humanoid robotics; Ionic memory; Memristor; Neuromorphic; Nociceptor; Transition-metal oxides; artificial nociceptors; electrochemical; ionic memory; memristor; transition metal oxides